Seedling nanopriming with selenium-chitosan nanoparticles mitigates the adverse effects of salt stress by inducing multiple defence pathways in bitter melon plants - Sheikhalipour, Morteza; Mohammadi, Seyed Abolghasem; Esmaielpour, Behrooz; Spanos, Alexandros; Mahmoudi, Roghayeh; Mahdavinia, Gholam Reza; Milani, Maryam Haghmadad; Kahnamoei, Amir; Nouraein, Mojtaba; Antoniou, Chrystalla; Kulak, Muhittin; Gohari, Gholamreza; et al. (My University, 2023)
Advances in the nanotechnology fields provided crucial applications in plant sciences, contributing to the plant performance and health under stress and stress-free conditions. Amid the applications, selenium (Se), chitosan and their conjugated forms as nanoparticles (Se-CS NPs) have been revealed to have potential of alleviating the harmful effects of the stress on several crops and subsequently enhancing the growth and productivity. The present study was addressed to assay the potential effects of Se-CS NPs in reversing or buffering the harmful effects of salt stress on growth, photosynthesis, nutrient concentration, antioxidant system and defence transcript levels in bitter melon )Momordica charantia(. In addition, some secondary metabolite-related genes were explicitly examined. In this regard, the transcriptional levels of WRKY1, SOS1, PM H+-ATPase, SKOR, Mc5PTase7, SOAR1, MAP30, α-MMC, polypeptide-P and PAL were quantified. Our results demonstrated that Se-CS NPs increased growth parameters, photosynthesis parameters (SPAD, Fv/Fm, Y(II)), antioxidant enzymatic activity (POD, SOD, CAT) and nutrient homeostasis (Na+/K+, Ca2+, and Cl-) and induced the expression of genes in bitter melon plants under salt stress (p ≤ 0.05). Therefore, applying Se-CS NPs might be a simple and effective way of improving crop plants' overall health and yield under salt stress conditions.
Keywords: Abiotic stress; Chitosan; Medicinal plant; Nanotechnology; Signal transduction